Langley, Mexico And The United States - The Fragile Relationship - Cummins, Victoria (Teaching History: A Journal of Methods, 1992)
This brief volume focuses not so much on Mexican-United States relations since World War II as on the evolving interrelationship between the two countries and its effects on bilateral issues. Langley finds former Arizona Governor Bruce Babbitt's statement that "Mexico and the United States are united by geography and divided by history" summarizes the common interpretation of the basis for United States-Mexican relations.